Mengupas Kemampuan Pedagogik Guru Sekolah Menengah:Antara Dedikasi dan Inovasi Kelas - Reza Alinata; Pajarni Pajarni; Elis Setiawati; Ade Irma; Rena Revita (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to examine the implementation of teacher pedagogical competence in three secondary schools with different characteristics, namely SMP Negeri 3 Tapung, SMAN 1 Tambang, and SMAN 12 Pekanbaru. Pedagogical competence does not only include the ability to deliver material, but also reflects an understanding of student characteristics, contextual learning strategies, and effective and enjoyable classroom management. Using a qualitative approach, data were collected through semi-structured interviews and direct observations to explore the experiences of teachers, principals, and students in the daily learning process. The results of the study showed variations in the application of pedagogical competence influenced by social environmental factors, facilities, and teacher readiness to respond to changes in education policy. Despite facing challenges such as limited facilities and administrative burdens, some teachers were able to demonstrate high dedication and innovation in learning. This study provides a comprehensive overview of pedagogical practices in the field and is expected to be an input in formulating policies to improve teacher quality contextually and sustainably.